INFLUENCING FACTORS INVESTMENT DECISION IN GENERATION Z (CASE STUDY ON FEB BANDAR LAMPUNG UNIVERSITY STUDENTS) - Clarissa Tiara Putri; Herry Goenawan Soedarsa (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Finance has now become one of the most important livelihood goals for everyone, and to meet daily needs, everyone needs money. Investing is one way to allocate capital for future profits. Investment decisions are influenced by various factors. The aim of this research is to find out and analyze the factors that influence investment decisions in Gen-Z. The population in this study were active undergraduate students at the Faculty of Economics and Business, Bandar Lampung University. Sampling used a purposive sampling method with the criteria of having made an investment, with a sample size of 100 people. This study uses Multiple Linear Regression analysis and uses the SPSS 26 application to process the data. The results obtained are that rational and irrational attitudes have a positive and significant partial or simultaneous effect on investment decisions. These results show that undergraduate students at the Faculty of Economics and Business, Bandar Lampung University, as Gen-Z, already have a good understanding of financial literacy, and have self-confidence based on their skills and knowledge, so they are confident that their investments will meet expectations.